2009
DOI: 10.1007/s12032-009-9186-z
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant chemoradiotherapy with cisplatin and docetaxel followed by surgery and consolidation chemotherapy in patients with unresectable locally advanced non-small cell lung cancer

Abstract: Preoperative concomitant chemoradiation using weekly cisplatin and docetaxel followed by surgery and consolidation chemotherapy is effective and well tolerated in patients with unresectable locally advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…With the development of radiation techniques, however, renewed enthusiasm is being given to hypofractionation. In the present study, the toxicity profile of our CCRT (with standard RT) cohort paralleled other studies with similar the raputic protocols (15)(16)(17)(18). Although concurrent CHT studies have found that weekly docetaxel and cisplatin was associated with relatively low toxicity and good compliance (4), in our study toxicities were significantly worse when compared with the SCRT group.…”
Section: Discussionsupporting
confidence: 82%
“…With the development of radiation techniques, however, renewed enthusiasm is being given to hypofractionation. In the present study, the toxicity profile of our CCRT (with standard RT) cohort paralleled other studies with similar the raputic protocols (15)(16)(17)(18). Although concurrent CHT studies have found that weekly docetaxel and cisplatin was associated with relatively low toxicity and good compliance (4), in our study toxicities were significantly worse when compared with the SCRT group.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, high levels of grade 3 esophagitis and pneumonitis were noted in chemotherapy protocols without 3-D conformal and IFI [26,27]. However, it has also been shown that dosimetric factors such esophageal volume treated above 45–50 Gy are risk factors for developing esophagitis [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, they had higher response and survival rates, which may related with success of surgery. [32] The only difference with the study of Nakamura et al . was higher dose of cisplatin; we found higher response rate, However, our survival rate was lower.…”
Section: Discussionmentioning
confidence: 92%
“…In phase I/II studies employing docetaxel and cisplatin concomitantly with radiotherapy, median survival rate was reported as 10.5-27 months and dose limiting toxicity was determined as esophagitis with various doses and administrations. [162628–32] …”
Section: Discussionmentioning
confidence: 99%